CODE SWITCHING AND CODE MIXING IN IAIN PONOROGO’S LECTURERS COMMUNICATION - Rizqi Akbarani (Institut Agama Islam Negeri (IAIN) Ponorogo, 2023)
In daily life, we often communicate with others using different languages. As we know that every ethnic group in Indonesia have regional language so it makes people use their regional language as a daily language for communication. Sometimes, the difference of language for communication becomes an obstacle in the communication process. This condition of society certainly provides an opportunity for code mixing and code switching in communication. This research aimed to find out the code switching and code mixing form that happened in communication between lecturers of IAIN Ponorogo, both formal and informal. This research used a synchronic language research where this research conducted by observing language phenomena in a certain period of time. The research data were obtained using the listening method and the spoken method. The collected data were analyzed using the agih and equivalent methods. From the collected data, researcher found that code switching occurred in the form of language transfer from Javanese or other languages to Indonesian, from English to Javanese, and from English to Indonesia. Code mixing in lecturers' communication can be grouped into word insertion, phrase insertion and sentence insertion. Code switching can be found from Javanese code to Indonesian code. Besides, lecturers of IAIN Ponorogo used code mixing and code switching included regional language code like Javanese Ponorogo dialect, Javanese Surabaya dialect, Indonesian code, or English code.